Endothelial keratoplasty versus repeat penetrating keratoplasty after failed penetrating keratoplasty: A systematic review and meta-analysis. - Feng Wang; Tao Zhang; Yan Wei Kang; Jing Liang He; Shi-Ming Li; Shao-Wei Li (PLoS ONE)
Objective This study sought to compare graft survival, graft rejection and the visual acuity outcome of endothelial keratoplasty (EK) with repeat penetrating keratoplasty (PK) after failed PK. Methods A systematic literature search with subsequent screening of the identified articles was conducted to obtain potentially eligible randomized clinical trials (RCTs) and comparative cohort studies. To assess the methodological quality of the included studies, the Jadad Scale or Newcastle-Ottawa Scale (NOS) was used based on the study design. To calculate the pooled odds ratios (ORs) for graft survival, graft rejection and the visual acuity outcome with 95% confidential intervals (CIs), a fixed- or random-effects model was applied based on the heterogeneity across studies. Results Four comparative cohort studies (n = 649 eyes) comparing the outcome of EK with repeat PK after failed PK were included in this review. These studies were considered high quality, with NOS scores ranging from 6 to 9. The EK group showed a significantly lower risk of graft rejection than the repeat PK group [0.43 (95% CI: 0.23-0.80, P = 0.007)]. In addition, no significant differences were observed in a comparison of graft survival and visual acuity (P values ranged from 0.81 to 0.97 using the Der-Simonian and Laird random-effects model). Conclusions As an alternative to repeat PK, EK after failed PK allows for potential reduction of the risk of graft rejection; however, it does not appear to confer a significant advantage in graft survival or visual acuity.